Genotypic variation in growth and yield of blackgram (Vigna mungo) genotypes in response to increased carbon dioxide concentration - LAKSHMI, N JYOTHI; VANAJA, M; YADAV, S K; MAHESWARI, M; VAGHEERA, P; REDDY, P RAGHURAM; VENKATESWARLU, B (The Indian Journal of Agricultural Sciences, 2013)
A study was conducted with 13 genotypes of blackgram (Vigna mungo L. Hepper) under two levels of CO2, vizelevated (550 ppm) and ambient (370 ppm) in open top chambers (OTCs) to assess the variability in crop yield responses to elevated CO2. The results revealed an increase in plant height, number of branches, leaf area, total dry weight, pod number, pod weight and seed yield under enhanced CO2 conditions as compared to ambient CO2 condition. Total dry weight and pod weight per plant were the most important yield contributing attributes in both conditions. There was asignificant variety Ã— CO2 interaction for seed yield, ranging from 7.95% to 65.4% higher than at ambient CO2. Thepercentage increase in seed yield with elevated CO2 conditions was highest in T 9 (65.4%) followed by WBG 26 (60.3%), which are early varieties. The high-yielding variety LBG 645 (4.35g/plant) at ambient CO2 also responded to elevated CO2 (5.35 g/plant), with an increase of only 23%. Though the early variety (T 9) showed low yield as compared to long duration varieties as recorded in the ambient CO2 conditions, it is very pertinent as well as interesting here to note that these early varieties have recorded higher percentage of increase over control as compared to long duration varieties. This shows that the adaptability for change in climatic conditions especially with reference to higher CO2 levels was highest in the short duration variety as compared to late varieties indicating that a case to case study is essential for identifying the adaptable varieties to changing environment depending upon the candidature crop.